SURVEI KETERAMPILAN SERVIS BAWAH DAN SERVIS ATAS BOLA VOLI PADA EKSTRAKURIKULER SMKN 9 MUARO JAMBI - Regina Ingrasias Sidabutar; Tri Bayu Norito; Bangkit Yudho Prabowo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the underhand and overhand serve skills of volleyball extracurricular students at SMKN 9 Muaro Jambi. This research used a quantitative descriptive approach with a survey method. The sample consisted of 20 students who participated in the volleyball extracurricular program, selected using total sampling. Data were collected through volleyball serve skill tests, in which each student performed 10 underhand serves and 10 overhand serves. The data were analyzed using descriptive statistics, including total score, mean, median, mode, standard deviation, minimum score, maximum score, and skill category. The results showed that the underhand serve skill obtained a total score of 544, a mean score of 27.20, a minimum score of 20, a maximum score of 34, and a standard deviation of 3.86. Based on the skill category, 15 students, or 75%, were in the very good category, 4 students, or 20%, were in the good category, and 1 student, or 5%, was in the fair category. Meanwhile, the overhand serve skill obtained a total score of 578, a mean score of 28.90, a minimum score of 23, a maximum score of 38, and a standard deviation of 3.54. The category distribution showed that 18 students, or 90%, were in the very good category and 2 students, or 10%, were in the good category. These findings indicate that the students’ overhand serve skill was slightly higher than their underhand serve skill. Overall, the volleyball serve skills of extracurricular students at SMKN 9 Muaro Jambi were in the good to very good category, although structured and continuous training is still needed to improve accuracy, consistency, and movement stability.